The Use of Gadgets on Ethics of Early Childhood Communication From the Perspective of the Qur'an - Moh. Abdan Syakuro; Ardhana Reswari; Danang Prastyo (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The Qur'an guides us to always speak kindly and gently to everyone. The purpose of this study is to describe the use of gadgets on communication ethics in early childhood in the perspective of the Qur'an. This type of research uses descriptive qualitative case study approach. The subjects involved in this study were 17 children aged class B2, teachers, and parents of students at RA An-Najah I. Data collection in the study was carried out using interviews, observation, documentation studies, and data identification with research instruments in the form of guidelines interviews and observations. Researchers used three stages in analyzing data which included reduction, data presentation, and drawing conclusions. The results of the study show that: the use of gadgets has an influence on children's communication ethics. Negative communication ethics that arise due to the use of gadgets in early childhood in the form of a very bad way of communicating with parents, namely by speaking in a harsh tone to parents, teachers and fellow peers which is contrary to the context of communication ethics according